Single and dual effects of different cytokinins on shoot multiplication of different apple scions - Dobránszky, J.; Abdul-Kader, A.; Magyar-Tábori, K.; Jámbor-Benczúr, E.; Bubán, T.; Szalai, J.; Lazányi, J. (International Journal of Horticultural Science, 2000)
Shoot multiplication responses of three apple scions to different concentrations of BA and BAR as single source of cytokinins and in combination with two concentrations of KIN were studied. The effects of hormones depended on genotype, type and interactions of different cytokinins. Use of BAR significantly enhanced the shoot multiplication of cv. Jonagold (6.5 shoots per explant). The multiplication rate of cv. Jonagold could not be improved by using the combination of BAR and KIN. The best proliferation was achieved by 1.0 mg 1-1 BA combined with 1.0 mg 1-1 KIN of cv. Prima..(8.1) and of cv. Galaxy (10.4).The effect of 0.5 mg 1-1 BA along with 1.5 mg 1-1 KIN was similar on multiplication rate (10.9) of cv. Galaxy.